Seismic Responses of a High-speed Railway (HSR) Bridge and Track Simulation under Longitudinal Earthquakes - Wei, Biao; Wang, Wei-Hao; Wang, Peng; Yang, Tian-Han; Jiang, Li-Zhong; Wang, Teng (Journal of earthquake engineering : JEE, 2022)
The seismic vulnerability of high-speed railway (HSR) bridges may be overestimated or underestimated when the track structure is oversimplified in a finite element model. Thus, the author established a track-bridge model considering CRTS II slab ballastless track and a trackless-bridge model. The effect of track constraint on the seismic vulnerability of various bridge components and overall system was evaluated by comparing the seismic vulnerability curves of different models under longitudinal earthquakes. The track structure itself was also evaluated, and the multiple components of the track structure were found to be under threat of seismic damage and needed seismic risk assessment.